دراسة مورفولوجية وفيزيولوجية لبعض طرز الأجاص السوري Pyrus syriaca. Boiss في منطقة القرداحة (مجلة جامعة اللاذقية- سلسلة العلوم البيولوجية, 2014)
أجريت الدراسة على نوع الكمثرى السورية Pyrus syriaca. Boiss المنتشر بشكل بري في منطقة القرداحة في محافظة اللاذقية خلال عامي 2013-2012م . تمت دراسة 9 طرز مظهرية منتشرة في مواقع مختلفة (عين العروس – ديرحنا - بسين) حيث بينت النتائج وجود اختلافات في بعض الصفات من أصل 13 صفة مظهرية مدروسة . اذ أظهر التحليل العنقودي انقسام الطرز المدروسة إلى مجموعتين رئيسيتين : ضمت المجموعة الاولى الطرز ( P1,P2,P3,P4,P5,P6 )  بينما ضمت المجموعة الثانية الطرز P7,P8,P9)). بدورها انقسمت المجموعتان الرئيسيتان  إلى تحت أربع مجموعات والتي يمكن اعتبارها طرزاً مظهرية مستقلة كمايلي : الرئيسية الأولى وضمت تحت المجموعة الأولى والثانية بقيم تشابه 0.62 حيث شملت تحت المجموعة الأولى الطرز( P1,P2,P3,P4,P5 ) مرموز لها بالرمزA  , وتحت المجموعة الثانية  P6 المرموز لها بالرمز B. الرئيسية الثانية : ضمت أيضاً تحت مجموعتين بقيم تشابه 0.77 شملت تحت المجموعة الأولى الطرز P7,P9 المرموز لها بالرمز  C وتحت المجموعة الثانية P8 المرموز لها بالرمز D. كذلك اظهرت الدراسة وجود تباين في نسبة إنبات بذور الطرز المدروسة اذ حققت بذور وأجنة الطراز P9 أعلى نسبة إنبات  , في حين أعطت بذور وأجنة الطراز (P6) أسرع نسبة إنبات .A study was conducted on one type of Syrian pears ‘Pyrus syriaca. Boiss’ which is widespread in Al-Qardahah area/Lattakia during 2012-2013. 9 superficial models were studied, these are scattered in different locations (Ein Al Aaros , Derhana, and Bsin). The results revealed the existence of differences in some of the characteristics, out of 13 morphological studied characteristics. A cluster analysis showed a division in the studied models. Two main groups can be distinguished: the first group included the following models (P1, P2, P3, P4, P5, P6), whereas the second group included the following models (P7, P8, P9). These two main groups are further divided into 4 subgroups which can be considered independent morphological Models. The first main group contains the first and second subgroups with a similarity value 0.62. The first subgroup contains P1, P2, P3, P4, P5, and it is symbolized as A; while the second subgroup contains P6 and it is symbolized as B. The second main group contains the first and second subgroups with a similarity value 0.77. The first subgroup contains P7, P9 and it is symbolized as C; whereas the second subgroup contains P8 symbolized as D. The research indicates that there is a difference in the seed germination percentage of the studied models. The seeds and embryos of P9 gave the highest germination percentage, while the seeds and embryos of P6 gave the fastest germination percentage.